Exploring Regional Potential to Strengthen Income in the Framework of Welfare Community - JAINAH, Z.O.; LINTJE, A.M.; ERLINA, B.; SUMBAWANINGRUM, H.R. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study aims to investigate the regional potential to strengthen original local income in the framework of the welfare community based on local wisdom. The author used the juridical normative approach and empirical. As a result, the role of society, in general, is to participate in maintaining a good environment, conducive security, friendly and earthy as in the rules of the tour like a charm. In conclusion, the potential management tourism in Pahawang Island is located in a bay where the waters are so clear, making the beauty of the sea around the island quite fascinating.RESUMEN El estudio tiene como objetivo investigar el potencial regional para fortalecer el ingreso original local en el marco de la comunidad de bienestar basado en la sabiduría local. El autor utilizó el enfoque jurídico normativo y empírico. Como resultado, el papel de la sociedad, en general, es participar en el mantenimiento de un buen ambiente, seguridad propicia, amigable y terrenal como en las reglas de la gira como un encanto. En conclusión, el turismo de gestión potencial en la isla de Pahawang se encuentra en una bahía donde las aguas son tan claras, lo que hace que la belleza del mar alrededor de la isla sea bastante fascinante.